Relationship of Creativity and Critical Thinking to Pattern Recognition Among Singapore Private School Students. - Daniel Ling, Meng Kay; Loh, Sau Cheong (Routledge Taylor & Francis Group, 2020)
Cognitive pattern recognition is known to be an important skill for academic subjects such as mathematics, science, languages, or even humanities. In this study, we investigate the relationships between creativity, critical thinking, and pattern recognition among 203 private school students, in Singapore. The instruments used include a creativity test (modified Creativity Selected Elements Questionnaire), a Critical Thinking Test (modified Cornell Critical Thinking), and a pattern recognition test. The main data analysis is done using the SMART-PLS structural equation modeling software. The results of the study reveal that creativity is a weak predictor of pattern recognition (b¼0.131, p>0.05, f2 ¼ 0.024) but critical thinking is a good predictor (b¼0.517, p<0.05, f2 ¼ 0.374). An implication of the research outcome is that more training on critical thinking should be given to the students to improve their pattern recognition ability.